SHAPE OF FEMININITY IN THE TEXT OF GEGURITAN (PHILOSOPICAL VERSE) IN BALI: ANALYSIS OF FEMINISM - Karmini, Ni Nyoman; Kutha Ratna, Nyoman; Weda Kusuma, I Nyoman; Suarka, I Nyoman (e-Journal of Linguistics; Vol. 3. 1 Januari 2009 No. 1, 2009)
The object of this study is Balinese traditional literature which is the form of geguritan(philosophical verse). The reason why such texts are used as the object of the study is that theycontain very complex and interesting narrations about feminism. The objectives of this studyare to find out the formal and narrative structure of the texts and to describe the shape offemininity in the texts and its relevance to the lives of Balinese women who are Hindufollowers in the society. The objectives are all at once the answers to the problems of the study.The theory applied is that of feminism which emphasizes the concept ofRadical-Cultural Feminism. This study is a qualitative one of which the data were collected bydocumentation method, that is, by the techniques of note taking, observation and interview. Thedata were analyzed using the formal method in accordance with literature studies.There were nine geguritan (philosophical verses) which were used as the object of thestudy. From the formal structural analysis, the pupuh (strophe) used, its function and literarystyle could be identified. From the content, religious and amusement functions could beidentified. From the narrative structural analysis, it could be identified that the plot waschronological and sorot balik (backward directed); the characters and characterization weredescribed to express extraordinary ability, which was based on Hinduism, while the theme wasdescribed to express the application of panca crada (the five principles in Hinduism). Therewere seven findings as far as the analysis of the text is concerned: they are: (1) the educatedwomen could determine their attitudes, make decisions, show prestige and maintain theirdignity; (2) the women in the texts had extraordinary power. This means that the women werenot weak. Therefore, the stereotype that women were weak was neglected; (3) the educatedwomen who used Hinduism as the reference could become the men’s power; (4) the womenwho could become the men’s power could be the centre or the subject of the events undergoneduring their lives; (5) the women’s ability was similar to the men’s and they could show theirability; (6) the shape of femininity in the texts was in accordance with wadhu tatwa ( a type ofphilosophy ) and the struggle of Radical Cultural Feminism; (7) it turned out that the theory offeminism could be used for analyzing the traditional literature.
Keywords: shape of femininity, geguritan (philosophical verse), feminism